Management of Adenoid Cystic Carcinoma of the Breast: A Single-Institution Study - Zhang, Wenxiang; Fang, Yi; Zhang, Zhihui; Wang, Jing (Frontiers in Oncology, 2021)
Objective The purpose of our study was to analyze the clinicopathologic features and surgical and oncological outcomes of adenoid cystic carcinoma (ACC) of the breast and to provide the basis for a clinical therapeutic schedule. Methods A total of 14 patients with primary breast adenoid cystic carcinoma treated at Cancer Hospital of the Chinese Academy of Medical Sciences from January 2000 to December 2017 were included. Data on clinical presentation, treatment strategy, and outcome, as well as the pathological features of ACC, were reviewed and analyzed. Results Fourteen patients were diagnosed with ACC of the breast, out of 23205 total patients treated for breast cancer (0.06%). All but three patients were postmenopausal, with a median age at diagnosis of 60.5 years (range, 39–73 years). The most common clinical presentation was a palpable mass (85.7%), and the imaging characteristics of all patients on color Doppler ultrasound and mammography were nonspecific. Six patients (42.9%) were suspected of having ACC by fine-needle aspiration cytology (FNAC) and were confirmed by postoperative histology and immunohistochemistry. All 14 patients underwent surgery, and no patient had a positive lymph node status. Median tumor size was 1.75 cm (range, 1–3 cm). Eight/14 (57.1%) patients were hormone receptor negative (HR−) and HER-2/neu (−) (HER2−). The remaining patients were hormone receptor positive (HR+). There was no significant difference in clinicopathological characteristics between the HR+ group and the HR- group (P>0.05). The mean follow-up period was 57 months. Local recurrence occurred in 14.3% of patients, 1.7% of patients had distant metastasis, all patients with local recurrence or distant metastasis were in the HR (-) group, and all patients were alive at the last follow-up. Conclusion ACC of the breast cannot be simply summarized as triple-negative breast cancer because it also includes a small number of hormone receptor-positive breast cancers. Establishing a preoperative diagnosis is difficult on the basis of clinical imaging examination, FNAC may be useful tool in the diagnosis. the final diagnosis can only be assessed based on the results of the histopathological and immunohistochemical examination. Breast-conserving surgery may be an alternative treatment strategy, and axillary lymph node dissection or sentinel node biopsy may not be necessary in some cases.